KEEFEKTIFAN PEMBELAJARAN AL-QUR’AN HADITS MELALUI MODEL PEMBELAJARAN THINK PAIR SHARE BERBANTUAN CD (Universitas Negeri Semarang, 2012)
Based on the writer’s preliminary observations in MTsN 2 Kudus, most of the Al- Qur’an Hadits teachers on nun sukun materials still used lecturing method, small group discussion, question and answer. These methods has not yielded a maximum result so that the students tend to be passive and bored in the class. It led student lack of enthusiasm for learning and then the learning outcome did not worked optimally. Regarding these problems, the teacher should give variation in learning, especially in learning methods to improve the activity and students’ learning outcomes through cooperative learning. The cooperative learning has several models. One of them is TPS model assisted by interactive CD. In this learning model, students are divided into some groups. The members must be heterogeneous. In each group, the members must cooperate and help each other to master the material. The objectives of this study are to determine: 1) the level of learning achievement of completeness, 2) the increasing of learning outcomes.This study used Thiagarajan research & development design with four stages of media development. Media was developed to obtain the better level of interest and effectiveness of instructional media and have been tested through the process of testing with the total sample of 98 learners (15 learners were in the small test group, 83 learners were in the field test). Data collection techniques used in this study were observations, questionnaires and test method. Data analysis used one sample t-test, two-sample t-test, and simple linear regression test. The results showed that: 1) the learning outcomes of Al-Qur’an Hadits learning on nun mati/ tanwin achieved completeness criteria, 2) student learning outcomes improved.The suggestions are: 1) in the Information and Communications Technology (ICT) era, there are a lot of learning media that can be produced by computer technology. Therefore, the teachers need to learn and master this computer-based learning technology,Berdasarkan observasi awal yang penulis lakukan di MTsN 2 Kudus diketahui bahwa metode pengajaran Al-Qur’an Hadits pada hukum bacaan nun sukun/tanwin yang masih sering digunakan adalah metode ceramah, diskusi kelompok kecil dan tanya jawab. Cara pengajaran ini belum memberikan hasil yang maksimal sehingga siswa cenderung pasif dan bosan dalam belajar. Hal inilah yang menyebabkan kurangnya semangat siswa untuk belajar dan akhirnya menyebabkan hasil belajar siswa tidak maksimal. Melalui metode Think Pair Share (TPS) dengan berbantuan CD interaktif ini siswa dibagi menjadi beberapa pasangan, anggotanya heterogen, tiap pasangan diharapkan dapat saling bekerjasama dengan temannya dan saling membantu untuk menguasai materi.Tujuan dari penelitian ini adalah untuk mengetahui: 1) tingkat ketercapaian ketuntasan belajar dan 2) peningkatan hasil belajar. Jenis penelitian yang digunakan adalah penelitian pengembangan (R&D) model Thiagarajan dengan 4 tahap pengembangan. Media yang dikembangkan telah melalui proses uji coba dengan total sampel 98 pebelajar (15 dalam ujicoba kelompok kecil, 83 dalam ujicoba lapangan). Teknik pengumpulan data pada penelitian ini menggunakan metode pengamatan, angket dan metode tes. Analisis data menggunakan uji t satu sampel, uji t dua sampel, dan uji regresi linear sederhana. Hasil penelitian menunjukkan bahwa: 1) hasil pembelajaran Al-Qur’an Hadits pada hukum bacaan nun sukun/tanwin mencapai kriteria ketuntasan; 2) hasil belajar siswa meningkat. Berdasarkan hasil dari penelitian maka penulis menyarankan para guru perlu belajar dan menguasai teknologi pembelajaran berbasis komputer ini.